WORKLOAD ANALYSIS FUNGSIONAL DAN MENTAL UNTUK JOB DESIGN - Mardiyanti, Ressy (Jurnal Psikologi, 2019)
AbstractThis study aims to determine the workload and needs of employees as a basis for the company to runan efficiency program. Based on management's assessment at the beginning of PT. ABC stated that in East Java Bali Nusra (EJBN) total of employees is very high, but the opinion of the head of the region is not true. This study is an applied research specifically evaluation research. The research subjects were taken by cluster sampling technique. The research location is PT. ABC especially the EJBN region with a total of 23 employees, headquartered in Surabaya. From the research, it is known several things, namely the procedures for preparing / reviewing job descriptions, workloads and employee needs for each position. Some functions underload work, such as Marketing Coordinator, Courier, Customer Relation Officer (security), Health Service Admin. Some are in the normal criteria, including the functions of Marketing, Support / admin marketing, Engineer marketing, Finance & Treasury Support, computer support spesialist, General Affair Coordinators, Drivers, Operational Coordinators, Customer Relation Officers (Bali, NTT, NTB, KAI, Janitor, etc.). The function that is in the overload criteria is in the Head of EJBN position, Treasury, Controllers, and Chief Financial Coordinator, Personal Recruiter, and Customer Relations Officer who handles Customer Service in one company. Based on these data, the researcher designed the intervention, namely making job design by means of job enrichment, job enlargement, and rotation. Key Words : job design, job description, workload AbstrakPenelitian  ini  bertujuan  untuk  mengetahui  beban  kerja  dan  kebutuhan  pegawai  sebagai  dasarperusahaan menjalankan program efisiensi. Berdasarkan penilaian manajemen diawal PT. ABC menyatakan diwilayah East Java Bali Nusra (EJBN) sangat banyak jumlah karyawannya, akan tetapi pendapat kepala wilayah, hal tersebut tidak benar. Penelitian ini merupakan applied research khususnya evaluation research. Subyek penelitian diambil dengan teknik cluster sampling. Lokasi penelitian adalah PT. ABC khususnya wilayah EJBN dengan total pegawai sebanyak 23 orang, yang berkantor pusat di surabaya. Dari penelitian diketahui beberapa hal yaitu mengenai tata cara penyusunan/ review job description, beban kerja dan kebutuhan karyawan pada masing-masing jabatan. Beberapa fungsi mengalami underload pekerjaan yaitu Marketing Coordinator, Courier, Customer Relation Officer (Satpam), Admin Health Service. Beberapa berada pada kriteria normal, diantaranya fungsi Marketing, admin/ support marketing, engineer marketing, Finance & Treasury Support, General Affair Coordinator, Driver, Operational Coordinator, Customer Relation Officer (Bali, NTT, NTB, KAI, Janitor, dll). Fungsi yang berada pada kriteria overload ada di jabatan Head of  EJBN,  Treasury,  Controllers,  and  Chief  Financial  Coordinator,  Personal  Recruiter,  dan Customer Relation Officer yang menangani Customer Service disalah satu perusahaan. Berdasarkan data tersebut, maka peneliti membuat rancangan intervensi yaitu membuat job design dengan cara job enrichment, job enlargement, dan rotasi. Kata Kunci : analisis pekerjaan, desain pekerjaan, deskripsi pekerjaan